Economic Impact of Live Streaming Commerce on Small and Medium-sized Enterprises - Jaunghyun Hwang; Donggeun Kim; Alex Jiyoung Kim; Junghwan Kim (International Telecommunications Society (ITS), 2024)
This study investigates the adoption of live streaming commerce among the small and medium-sized enterprises (SMEs) in South Korea. While most previous research has focused on consumer perceptions such as intention to watch live streaming and buy products, this research examines sellers' issues that are mostly SMEs by focusing on SMEs' adoption of live streaming commerce and changes on their sales. Specifically, we analyze actual sales data of 32 SMEs that were recruited and had no prior live streaming commerce experience. By comparing SMEs' performance before and after adoption of live streaming commerce, we find that most of performance metrics such as a number of buyers, a number of payments, revenue per sale, and a number of items sold per sale all improve after the adoption of live streaming commerce, highlighting the potential of live streaming commerce to enhance SME performance. These findings suggest that live streaming commerce can help SMEs as an effective tool to strengthen SMEs' digital marketing capabilities. We also provide policy implications for SMEs and regulatory organizations about how they can effectively utilize live streaming commerce.
Keywords: 330; Live Streaming Commerce; Digital Transformation; Small and Medium-sized Enterprises (SMEs); Business Performance; E-commerce